Assessing the impact of Scrum in airborne software quality assurance - Fernandes, Fernanda C. P. Motta; França, Ricardo Bedin (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2015: Anais do XIV Simpósio Brasileiro de Qualidade de Software, 2015)
In this paper, we present an evaluation of Scrum's impacts over the software quality assurance process in the embedded aerospace software domain. We present basic concepts of the DO-178C and Scrum, then we assess related work and introduce the case study used as reference for our study, as well as the perceived results of using Scrum in both the development teams and in quality assurance. Finally, we summarize good practices for using Scrum in software quality assurance teams.